The Influence Of Experimental Methods Against The Process Skills Science Grade IV Elementary School Yogyakarta Golo - Ade, Rulianinta (APTISI Transactions on Management (ATM), 2019)
This study descriptively aims to find out the tendency of students science process skills by using experimental method and demonstration method and comparatively to find out the differences of students science process skills by using experimental method and demonstration method. The type of this study was quasi experiment. Data collection techniques used observation, test and documentation. Data analysis techniques used t-test that was started by normality test and homogeneity variant test. The results of the descriptive study showed that the tendency of the students science process skills used the experimental method were in high categories, while the demonstration method was in the medium category. Comparatively there was very significant difference of science process skills by using the experimental method and the demonstration method. The average of science process skills of the experiment method.